The Impact of Delays in Interfaculty Transfer on Outcomes in Elderly Trauma Patients. Issue 7 (July 2022) - Quinn, Seth A.; Edwards, Jacob D.; Buccini, Peter; Parmley, Michael K.; Leonard, Kenji; Irish, William; Toschlog, Eric A.
Background: Delay to definitive treatment is a significant and persistent challenge to trauma systems across the United States, especially in rural communities with limited resources. We hypothesized that elderly trauma patients with delay in transfer would have increased morbidity and mortality. This study evaluates the relationship between inter-facility transfer time and outcomes in elderly trauma patients, and the validity of the 4-hour dwell time as a performance improvement benchmark. Methods: The National Trauma Registry and Emergency Medical Services Database were queried from January 2010 to January 2018. Inclusion criteria included age ≥65, blunt mechanism, and transfer from another facility. Correlation analysis was used to evaluate the association between clinical and demographic variables and transfer time. Multicollinearity was evaluated using the variance inflation factor. Results: 1535 patients were identified. This cohort was further subdivided into 4 cohorts based on dwell time: 0-1.5 hours (n = 384), ≥1.5-1.9 hours (n = 379), 1.9-<2.5 hours (n = 383), and ≥2.5 hours (n = 388). Analysis revealed that shorter dwell time was associated with male gender ( P = .0039), higher ISS (injury severity score) ( P < .0001), lower RTS (revised trauma score) ( P < .0001), higher pre-hospital arrest ( P = .0066), lower initial GCS (Glasgow Coma Scale) ( P = .0012), higher mortality, longer ICU, and ventilator length of stay ( P < .0001). Longer dwell times were associated with discharge from the hospital to home or skilled nursing facility as well as lower mortality ( P < .0001). Discussion: Longer dwell time was inversely related to outcome. More severely injured patients were rapidly transferred. This represents a mature rural trauma system. In addition, dwell time should be scrutinized as a meaningful indicator within a performance improvement program.